Improving Nursing process Performance based on service scheduling dimensions. ( Field research) - داود, فضيلة سلمان; نعيمة, فيصل علاوي (Journal of Economics and Administrative Sciences, 2016)
Abstract :This present paper sheds the light on dimensions of scheduling the service that includes( the easiness of performing the service, willingness , health factors, psychological sides, family matters ,diminishing the time of waiting that improve  performance of nursing process including ( the willingness of performance, the ability to perform  the performance , opportunity of performance) . There is genuine problem in the Iraqi hospitals  lying into the weakness of nursing staffs , no central decision to define and organize schedules. Thus the researcher has chosen  this problem as to be his  title . The research come a to develop  the nursing service schedules  and improving  performance of nursing services  submitted in the Iraqi hospitals in addition to adhering  international standards and  scientific methods application as to contribute into raising  its level  to highest one suited to international one. Conducted research on a sample of the Angels nursing working in the Martyr al-Sadr General Hospital, has reached the research sample (100) person included Angels Nursing, The research was adopted to test the hypotheses of correlation and influence between the variables mentioned in the hospital Martyr al-Sadr, has been a resolution the primary means of gathering information adopted by the researcher as well as quantitative data.For the purpose of data analysis variables Find researcher based on the arithmetic mean, standard deviation, the difference and the relative importance coefficient, rank correlation coefficient, simple regression coefficient, the coefficient of determination.It has been reached to set of conclusions was the most important that the surveyed hospitals do not take into consideration the psychological, social and health conditions of the cadres of nursing in the preparation of scheduling nurses on according to night shifts and day-system, and reached a number of recommendations, most notably the need to study the martyr Sadr Hospital management dimensions of service scheduler that have been addressed prior to the preparation of nursing staffs tables and so what of those dimensions of a direct impact on improving the performance of the nursing process